1984
DOI: 10.1177/014662168400800201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Local Item Dependence on the Fit and Equating Performance of the Three-Parameter Logistic Model

Abstract: Unidimensional item response theory (IRT) has become widely used in the analysis and equating of educational achievement tests. If an IRT model is true, item responses must be locally independent when the trait is held constant. This paper presents several measures of local dependence that are used in conjunction with the three-parameter logistic model in the analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
500
1
11

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 531 publications
(519 citation statements)
references
References 8 publications
7
500
1
11
Order By: Relevance
“…Local independence of the DESIGMA items was tested using Yen's Q 3 statistic [47]. The latter tests the absence of meaningful pair-wise correlations of item residuals after controlling for person ability and item difficulty.…”
Section: Preliminary Checks and Data Preparationmentioning
confidence: 99%
“…Local independence of the DESIGMA items was tested using Yen's Q 3 statistic [47]. The latter tests the absence of meaningful pair-wise correlations of item residuals after controlling for person ability and item difficulty.…”
Section: Preliminary Checks and Data Preparationmentioning
confidence: 99%
“…Previous research has demonstrated the reasonableness of the three-parameter logistic model for the GRE verbal and quantitative measures (Kingston and Dorans, 1982a). Analysis of item-ability regressions (for an example of such an analysis see Kingston and Dorans, 1985) and a slightly modified Yen's Q 1 statistic (see Yen, 1981Yen, , 1984 indicated that the three-parameter logisfic model is probably reasonable for the current GRE General Test.…”
Section: Factors That May Have Affected These Resultsmentioning
confidence: 91%
“…Thus, the current study expands and improves the work of Thomas et al (2016) In the following sections, techniques that yield item properties that may be useful in detecting item compromise will be introduced and described including: Rasch model estimates, three-parameter logistic (3PL) IRT model estimates, item response times, Yen's (1984) Q3 for identifying local dependence of items, and linear logistic test model (LLTM) estimates. Then the methods for using these item properties and the suspected item categories to create functions that can separate compromised items from uncompromised items, which, in the current study, are Support Vector Machines (SVMs) will be discussed.…”
Section: List Of Figuresmentioning
confidence: 87%
“…Thomas et al (2016) suggest that examinees with pre-knowledge may have response patterns that are identifiable by their item response times and correctness of item responses. Examinees with pre-knowledge may respond more quickly to suspected compromised items than to other items, because they were previously exposed to these items, and thus may spend less time reading and responding to them (Marianti, Fox, Avetisyan, Veldkamp, & Tijmstra, 2014 Therefore, in the current study, Yen's Q3 statistic (Yen, 1984) for local dependence (LD) was calculated to use as an item feature that quantifies violations of this assumption.…”
Section: Item Response Timesmentioning
confidence: 99%
See 1 more Smart Citation